Effect of long-term treatment with insulin and/or acarbose on glomerular basement membrane thickening in alloxan-diabetic rats - Macedo, C. S. [UNESP] (1996)
Acarbose is a competitive inhibitor of the intestinal alpha-glycosidases, that can delay absorption of intestinal carbohydrates causing their malabsorption. In the present paper we studied the effects of insulin, acarbose and their association on glomerular basement membrane thickening in alloxan-diabetic rats. Twenty-five male and female Wistar rats, approximately 3 months old at the beginning of the experiment, were assigned randomly to each of five experimental groups: normal contrl rats, alloxan-diabetic control rats, alloxan-diabetic rats heated with acarbose, alloxan-diabetic rats treated with insulin, and alloxan-diabetic rats treated with insulin plus acarbose. Alloxan was administered in a single iv dose of 42 mg/kg body weight. Insulin was given subcutaneously at doses of 18 to 30 IU/kg corrected daily on the basis of glycosuria and ketonuria. Acarbose was given mixed with rat chow in a dose of 50 mg/100 g chow. Body weight, water and food intake and diuresis, as well as bloed and urine glucose were determined after 1, 3, 6, 9, and 12 months of treatment. Glomerular basement membrane (GBM) thickening was determined by electron microscopy at the same times. Clear clinical and laboratory signs of severe diabetes, with blood glucose levels above 200 mg/dl and urine glucose above 3000 mg/dl, were observed in all alloxan-diabetic control rats, in all periods of follow-up, whereas administration of insulin or acarbose reduced the blood glucose levels of treated groups. The most satisfactory control of blood and urine glucose was observed in animals treated with both insulin and acarbose. However, diarrhea was observed in diabetic rats treated with acarbose associated or not with insulin. GBM thickening was correlated with age in all groups. Beginning at six months after diabetes induction, the GBM of untreated diabetic rats was significantly thicker (mean ± SEM, 4.446 ± 0.45 mm) than that of normal rats (2.977 ± 0.63 mm). Both insulin and acarbose prevented GBM thickening and their combination induced thickening similar to the age-dependent thickening observed for normal rats of the same age. We conclude that acarbose when combined with insulin may be a good option in the control of diabetes and its renal complications.